2001
DOI: 10.1115/1.1383973
|View full text |Cite
|
Sign up to set email alerts
|

NO x and N2O Formation Mechanisms—A Detailed Chemical Kinetic Modeling Study on a Single Fuel Particle in a Laboratory-Scale Fluidized Bed

Abstract: NO x (i.e., NO and NO2) and N2O are known as harmful pollutants. In fluidized bed combustion these are formed from the nitrogen in the fuel. To develop effective primary measures reducing the emissions, more knowledge on the mechanism of formation and destruction ongoing in fluidized beds has to be obtained. In this work, a detailed chemistry model is combined with a two-phase model for a stationary fluidized bed to calculate the emissions of a single fuel particle in a laboratory-scale stationary fluidized be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The slope of each line represents the reaction order v. The correlation shows, for all kinds of tested bed materials, the reaction order is close to unity, i.e., v = 1.0. The result is the same as that for the homogeneous thermal decomposition, which was found to be quite close to a first-order reaction [1,[18][19][20].…”
Section: Kinetic Parameters For N 2 O Decomposition Over Each Surrogatesupporting
confidence: 73%
“…The slope of each line represents the reaction order v. The correlation shows, for all kinds of tested bed materials, the reaction order is close to unity, i.e., v = 1.0. The result is the same as that for the homogeneous thermal decomposition, which was found to be quite close to a first-order reaction [1,[18][19][20].…”
Section: Kinetic Parameters For N 2 O Decomposition Over Each Surrogatesupporting
confidence: 73%
“…However, most of NOx is formed during char combustion for both two types of coal. This is because most of NOx is formed by heterogeneous oxidation of char-N during char combustion, while N 2 O is formed by the homogeneous reaction of HCN [23].…”
Section: Base Case With T ¼ 1043 Kmentioning
confidence: 99%
“…It is well known that the ratio of HCN and NH 3 concentrations formed during fuel pyrolysis is very important for further fuel-N conversion, as these are the main precursors of nitrogen oxides. During devolatilization, NO is formed from HCN and NH 3 , while N 2 O is formed almost exclusively from HCN (Kilpinen and Hupa, 1991;Pels, 1995;Lö effler et al, 2001). Generally, in coal combustion, NH 3 is considered to be the most important volatile N-containing species in pyrolysis since measurements showed that NH 3 is usually present in higher concentration than HCN in the combustion chamber (Å mand, 1991).…”
Section: Introductionmentioning
confidence: 97%